2010
DOI: 10.1016/j.adolescence.2010.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Factors that influence the accuracy of adolescent proxy reporting of parental characteristics: A research note

Abstract: Socioeconomic status (SES) is considered to be an important marker of physical, mental, and social outcomes. However, methods used to gather socioeconomic information vary widely in terms of both the indicators of SES used (e.g., education, occupation, income, etc.) and data collection strategies. In particular, studies of adolescents often rely on children's proxy reports of measures of parents' SES. There is disagreement in the literature regarding children's ability to reliably serve as proxy respondents fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
27
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 27 publications
3
27
0
2
Order By: Relevance
“…We also observed high levels of missing data on parental occupation, which were higher for less well-off adolescents 9 47. Analyses using multiple imputations methods for missing values in the ISCO scheme found no substantial difference in results.…”
Section: Discussionmentioning
confidence: 61%
“…We also observed high levels of missing data on parental occupation, which were higher for less well-off adolescents 9 47. Analyses using multiple imputations methods for missing values in the ISCO scheme found no substantial difference in results.…”
Section: Discussionmentioning
confidence: 61%
“…Children in lower grades tend to exaggerate the occupations of their fathers while children in the upper grade level at school report their fathers' occupation more accurately [18]. Research also showed that when children were asked to report on their mothers' income and to tell if the mothers received food stamps, the reports by children on their mothers' economic status also varied by the child's gender, age and race [16]. Children also exaggerate their parents' educational level [17].…”
Section: Discussionmentioning
confidence: 95%
“…The Principal Investigator observed that amongst the children in the main stream school, even if their father worked as a cleaner or an orderly in a hospital, the children insisted that their father was a doctor. This is not surprising because children idolize their fathers [16][17][18]. Several studies have shown inconsistencies between what the child reports as the parents' occupation and what the parents report as their occupation [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations